Further improvements of an extended Hakki-Paoli method. (September 2018) - Vanzi, M.; Mura, G.; Martines, G.
Abstract: A modified Hakki-Paoli method, for measuring optical gain in laser diodes, proposed at the past ESREF 2017 conference is here further improved in terms of practical implementation. In particular, averaging both the spectral function and its reciprocal, over an oscillation cycle is shown to lead to the gain function replacing the calculation of maxima and minima, a cumbersome task for noisy spectra at low injection level. The ultimate goal is to get rid of the many constraints that complicate gain measurements for other than the manufacturers, and to provide a new powerful tool for laser diode characterization and diagnostics. Highlights: Optical gain measurement in Fabry Perot laser diodes is made accessible even not knowing technological details. This is the third step of a stair. The first step is the Hakki Paoli method. The second a revision recently presented. This step gives a mathematical reinterpretation of the spectral data, that is physically sound and practical for calculation. The result is an insight at great detail of the gain spectral function, and of its upper and lower boundaries. Gain, instead of intermediate quantities as the threshold current, becomes a practical monitoring a laser diode.